Equity evaluation of urban park system: a case study of Xiamen, China - Luo, Tao; Yang, Fengmei; Wu, Lianglong; Gao, Xihong (Journal of Environmental Engineering and Landscape Management, 2020)
Urban parks play a distinctive and important role in satisfying residents’ demands on leisure and recreation, and thus have become the focus of research in the field of urban planning and sustainable development. This paper used equity as indicator to combine both the supply and demand sides of urban park service. Taking Xiamen as the study case, the relationship between spatial distribution of population and park services was analyzed. The results show that while population density has a significant spatial relationship with urban park service level at the city scale, Xiamen has the problem of neglecting the equity of urban park service between people and regions within the city. The proposed approach builds up the linkage between urban park service and urban population in order to evaluate the performance of urban park. Although the mechanism remains to be discussed, this study provides a useful auxiliary tool for constructing a guideline for urban green space planning, since urban park is increasingly seen as a kind of restricted public resource and ensuring its equity should be an important task for city mangers.